Green Biocomposites Design and Applications - Jawaid, Mohammad; Salit, Mohd Sapuan; Alothman, Othman Y. (Cham Springer International Publishing, 2017)
This book introduces the concept, design and application of green biocomposites, with a specific focus on the current demand for green biocomposites for automotive and aerospace components. It discusses the mathematical background, innovative approaches to physical modelling, analysis and design techniques. Including numerous illustrations, tables, case studies and exercises, the text summarises current research in the field. It is a valuable reference resource for researchers, students and scientists working in the field of materials science
Green Biocomposites for Structural applications -- Green Composites: Versatile Material for Future -- Design and Fabrication of Green Biocomposites -- Cellulosic Biocomposites: Potential materials for future -- Conceptual design of biocomposites for automotive components -- Design of Prosthetic Leg Socket from Kenaf Fibre Based Composites -- Synthesis of Soy Protein Based Biocomposites for Packaging Applications -- Green Biocomposites: A Prospective Utilization in Automobile Industry -- Polylactic Acid Green Nanocomposites for Automotive Applications -- Bamboo Fiber-Polymer Composites: Overview of Fabrications, Mechanical Characterizations and Applications -- Biocomposite Materials and Its Applications in Acoustical Comfort and Noise Control -- Okra Fibers: Potential Material for Green Biocomposites -- Interface Interaction of Jute Fiber Reinforced PLA Biocomposites for Potential Applications.
Keywords: Materials Engineering; Renewable Energy; Materials; Chemistry, Technical; Renewable energy sources; Industrial Chemistry; Biomaterials